Islamic Microfinance and Digital Literacy Driving MSME Growth: Innovation as Mediator and Competition as Moderator in Shariah Economic Context - Nurfaizal, Yusmedi; Khafidin, Zaenal (IQTISHADIA, 2025)
This study investigates the impact of Islamic microfinance and digital literacy on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, grounded in the principles of maqāṣid al-sharīʿah. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) on a sample of 100 MSMEs, the study examines both direct and indirect effects through business innovation, with market competition as a moderating variable. The findings reveal that Islamic microfinance and digital literacy significantly promote MSME growth, while business innovation is a key mediating mechanism. Interestingly, the moderating effect of market competition on innovation is negative, suggesting that excessive rivalry may inhibit innovation outcomes. This result is interpreted through both Islamic principles, such as maslahah, musābaqah, and ijtihād, and conventional theories of competition and innovation. The integration of ethical constructs like akhlāq al-raqāmiyyah and sharia-compliant financing (e.g., muḍārabah, mushārakah) demonstrates how spiritual and strategic dimensions interact in entrepreneurial growth. The study contributes to Islamic entrepreneurship theory by formalizing ethical digital literacy and Islamic competition as empirical constructs. It offers practical insights for Islamic financial institutions and policymakers while supporting the Sustainable Development Goals, particularly Goal 8 on inclusive economic growth.